2
$\begingroup$

Consider the Legendre differential equation $$ (1-x^2) y'' - 2xy' + n(n+1)y = 0 $$ Then its solution is given by $$ y = c_1 P_n (x) + \text{an infinite series} $$ In fact $y = c_1 P_n (x) + c_2 Q_n (x) $ where $P_n$ is Legendre polynomials and $Q_n $ is Legendre function of the second kind. Here I want to prove that 'an infinite series' above can be written by $c_2 Q_n (x)$ for some constant $c_2$.

$\endgroup$
  • $\begingroup$ You should see this. $\endgroup$ – J. M. is a poor mathematician Jul 29 '12 at 4:15
  • $\begingroup$ @J.M. Thank you J.M., this proof is what I wanted. $\endgroup$ – Ann Jul 29 '12 at 4:31
3
$\begingroup$

The infinite series you are talking about stems from the recurrence relation that can be derived when solving the Legendre differential equation: plugging in $$y = \sum_{j=0}^{\infty}a_jx^j $$ into $$[(1-x^2)y']' + n(n+1)y = 0$$ you get $$\frac{a_{k+2}}{a_k} = \frac{k(k+1) - n(n+1)}{(k+1)(k+2)}$$ Obviously, this leads to separate solutions with all even or all odd powers of $x$. When $n$ is even, then starting with $a_0 \not= 0$, the series terminates and you get (a multiple of) $P_n$. The same holds for odd $n$ starting with $a_1 \not= 0$. But when n is even and we start with $a_1 \not= 0$, then the series does not terminate. For instance, for $n=0$, we get $$\frac{a_{k+2}}{a_k} = \frac{k(k+1)}{(k+1)(k+2)} = \frac{k}{k+2}$$ which clearly leads to (taking $a_1=1$) $$y= \sum_{k=0}^{\infty}\frac{1}{2k+1}x^{2k+1}$$ Now, as $$ln(1+x) = \sum_{j=0}^{\infty}\frac{(-1)^{j+1}}{j}x^j$$ it is easy to derive \begin{equation} \begin{split} ln(\frac{1+x}{1-x}) &= ln(1+x) - ln(1-x) \\ &=\sum_{j=0}^{\infty}\frac{(-1)^{j+1}}{j}x^j + \sum_{j=0}^{\infty}\frac{x^j}{j} \\ &=\sum_{j=0}^{\infty}\frac{(-1)^{j+1} + 1}{j}x^j \\ &= 2x + 2\frac{x^3}{3} + 2\frac{x^5}{5} + ... \end{split} \end{equation} which is twice what we are looking for. So $$Q_0(x) = \frac{1}{2} ln(\frac{1+x}{1-x})$$ Similarly, $$Q_1(x) = \frac{x}{2} ln(\frac{1+x}{1-x}) - 1$$ And the rest of the $Q_n$ can then be determined by using the recurrence relation $$(n+1)Q_{n+1}(x) = (2n+1)xQ_n(x) - nQ_{n-1}(x)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.